2016
DOI: 10.3390/molecules21101335
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Extraction, Preliminary Characterization and Antioxidant Activities of Polysaccharides from Semen Juglandis

Abstract: Abstract:The optimization extraction process, preliminary characterization and antioxidant activities of polysaccharides from Semen Juglandis (SJP) were studied in this paper. Based on the Box-Behnken experimental design and response surface methodology, the optimal extraction conditions for the SJP extraction were obtained as follows: temperature 88 • C, extraction time 125 min and ratio of liquid to solid 31 mL/g. Under these conditions, experimental extraction yield of SJP was (5.73 ± 0.014)% (n = 5), simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Recent reports have shown that Diaphragma juglandis fructus contains diverse bioactive components, including phenolic acids, flavonoids, saponins, quinones, alkaloids, and polysaccharides. Among these, phenolic acids and flavonoids are known as dietary polyphenols, which are widely found in plants or plant-derived foods such as fruits, vegetables, grains, tea, and wine . Dietary polyphenols exhibit a variety of activities, such as antioxidant, anti-inflammatory, antitumor, and cardiovascular-protective activities. However, to date, there has been neither a systematic and comprehensive description of the chemical composition nor a simultaneous quantitative analysis of multiple bioactive compounds, especially dietary polyphenols, in Diaphragma juglandis fructus.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have shown that Diaphragma juglandis fructus contains diverse bioactive components, including phenolic acids, flavonoids, saponins, quinones, alkaloids, and polysaccharides. Among these, phenolic acids and flavonoids are known as dietary polyphenols, which are widely found in plants or plant-derived foods such as fruits, vegetables, grains, tea, and wine . Dietary polyphenols exhibit a variety of activities, such as antioxidant, anti-inflammatory, antitumor, and cardiovascular-protective activities. However, to date, there has been neither a systematic and comprehensive description of the chemical composition nor a simultaneous quantitative analysis of multiple bioactive compounds, especially dietary polyphenols, in Diaphragma juglandis fructus.…”
Section: Introductionmentioning
confidence: 99%
“…•OH is recognized as the most reactive oxygen free radical, which is highly aggressive and virulent to cells, and is also the main factor of organism peroxidation. Compounds usually achieve antioxidant effects by reducing the generation of hydroxyl radicals or removing the generated hydroxyl radicals (Ren et al, 2016). ABTS is a water-soluble free radical initiator, which can be oxidized to green ABTS radical (ABTS• + ), with maximum absorption wavelength of 734 nm.…”
Section: Discussionmentioning
confidence: 99%
“…All parts of walnut showed antioxidant activity -research has been carried on leaves, husks, seeds, fruits, shells, pellicles and kernels. 10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] Several different methods were equally employed for assessing antioxidant activity of different parts of walnut tree -FRAP (Ferric Reduction Antioxidant Power), Hydroxyl Radical Scavenging assay, Nitric oxide scavenging activity, β-carotene linoleate model system, TEAC (Trolox Equivalent Antioxidant Capacity), ABTS assay (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid), DPPH radical scavenging activity assay and DPPH using EPR (Electron Paramagnetic Resonance). 10,16,17,[22][23][24][25][26][27][28][29] Both IC50 and EC50 appear as suitable for reporting antioxidant activity of different walnut parts.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies that connected antioxidant potential of different walnut parts to the concentration of phenols in plant material, we are tend to assume that antioxidant activity of our plant material is also a consequence of the total phenol content. [20][21][22][23][24][25][26][27][28][29] However, we observe a discrepancy between the value of antioxidant activity and the content of phenolic compounds. Antioxidant activity of plant material in our research is lower than reported data, while the content of phenols is higher than the reported data.…”
Section: Discussionmentioning
confidence: 99%